Optimal tax progressivity in unionised labour markets: Simulation results for Germany - Stefan Boeters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2010)
Changing the income tax progressivity in labour markets with collective wage bargaining generates a trade-off. On the one hand, higher progressivity distorts individual labour supply decisions at the hours-of-work margin, on the other hand, it reduces unemployment by exerting downward pressure on wages. This trade-off is quantitatively assessed using a numerical model for Germany. The model combines a microsimulation module, which captures the labour-supply decisions of approximately 4600 individual households, and a macro (computable general equilibrium) module, which features collective wage bargaining and involuntary unemployment. In the simulations carried out using this model, the optimal degree of tax progressivity turns out to be higher than the one in the actual German tax schedule. The optimum is located at marginal tax rates that are 6 percentage points higher than the actual rates (combined with a transfer that balances the public budget). The welfare gain from such a reform is modest, however. It amounts to no more than two euros per person per month.
Keywords: C63; C68; H21; J22; J51; J64; 330; labour taxation; tax progressivity; optimal taxation; collective wage bargaining; unemployment; microsimulation; computable general equilibrium model; Lohnsteuer; Steuerprogression; Optimale Besteuerung; Tarifpolitik; Arbeitslosigkeit; Arbeitsangebot; Mikrosimulation; Deutschland